Epidemiology of pediculosis capitis among schoolchildren in the eastern area of Bangkok, Thailand - Watcharawit Rassami; Mayura Soonwera (My University, 2012)
To determine the prevalence of infestation with head lice in primary schoolchildren in the eastern area of Bangkok, Thailand.The present study was to determine the head lice infestation (Pediculosis) levels in primary schoolchildren, during May, 2011 to July, 2011, A total of 3 747 schoolchildren aged 5-12 years old from 12 selected primary school of Ladkrabang district, the eastern area of Bangkok were examined for head lice. Pediculosis was defined as the presence of at least on living adult, nymph and viable egg.The overall head lice infestation rate was 23.32% and infestation rate was higher in girls (47.12%) than in boys (0%). The infestation rate among schoolchildren varied from 12.62% to 29.76%. The infestation rate among girls varied from 26.07% (12 years old group) to 55.89% (8 years old group).Pediculosis is a common public health problem affecting primary schoolchildren in eastern area of Bangkok and those levels are epidemic importance.
Keywords: Pediculosis; Dermatological diseases and infestations